Effect of Pelvicaliceal Anatomy on “Post Eswl Stone Clearance of Lower Caliceal Stone" (Bangladesh Journal of Urology, 2020)
Objective: To find out stone clearance rate of lower calyx and to determine important anatomic predictive factors responsible for the stone clearance of lower calyx following ESWL.Methods: This prospective quasi experimental study was conducted in the Department of Urology, Dhaka Medical College Hospital, Dhaka, from January 2006 to July 2007. Patients with single lower calyceal stone (Stone size d” 20mm), age between 12 to 75 years and were agreed to participate in the study were selected. Different lower calyceal predictive factors were measured from IVU with the help of radiologist before ESWL. Selected patients were treated with ESWL by siemens lithostar machine in the department of Urology, Dhaka Medical College Hospital. Patients were discharged on the same day with advice to follow up after 1 month. All patients were followed up with plain X- ray KUB region to see stone clearance. Purposive sampling methods were followed. Data were processed and analyzed using software SPSS (Statistical Package for Social Sciences).Results: Lower caliceal stones with favorable anatomy (infundibulo-pelvic angle e”700, infundibular length d” 30mm, infundibular diameter >4mm, and infundibular length to diameter ratio < 7) were stone free in cases and was statistically significant in stone clearance. But number of minor calices , caliceal pelvic height and stone morphology have shown no impact on stone clearance in this study.Conclusion: ESWL for lower caliceal stone should be recommended only those patients those have favorable anatomy for discharge of fragments.Bangladesh Journal of Urology, Vol. 15, No. 1, Jan 2012 p.6-10